1970
DOI: 10.3329/jom.v10i2.2815
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Iodine Status and Thyroid Function during Pregnancy

Abstract: Background: Pregnant ladies are most likely to develop relative iodine deficiency during pregnancy to affect thyroid function in our population unless specific dietary care or therapeutic iodine supplementation is taken into account which is yet to be materialized. Methods: In this cohort study sixty uncomplicated normal pregnant women were enrolled in 1st trimester and followed up till delivery. In every trimester maternal iodine status & thyroid status were determined by urinary iodine & serum thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Since the SCH is a biochemical diagnosis, the symptoms may be mild, non-specific and may mimic typical symptoms in pregnancy. The increase in serum TSH level with the advancement of pregnancy in our study was compatible with the findings of the study done in Bangladesh [ 9 ]. A recent study done on pregnant women (in their second trimester) in Iran showed that the prevalence of hypothyroidism in pregnant woman was 13.7 % and the prevalence of hyperthyroidism was 1.5 % [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Since the SCH is a biochemical diagnosis, the symptoms may be mild, non-specific and may mimic typical symptoms in pregnancy. The increase in serum TSH level with the advancement of pregnancy in our study was compatible with the findings of the study done in Bangladesh [ 9 ]. A recent study done on pregnant women (in their second trimester) in Iran showed that the prevalence of hypothyroidism in pregnant woman was 13.7 % and the prevalence of hyperthyroidism was 1.5 % [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, with the progression of pregnancy there was steady decline in maternal urinary iodine status and increase in deficiency status and the observed difference was highly significant ( p < 0.001). Such progressive decline in urine iodine level with the advancement of gestational age was quite compatible with the results of studies done in Bangladesh [ 9 ], Congo [ 10 ], Nigeria [ 11 ] and in some other countries too [ 12 14 ]. This reduction in UI concentration can be attributed to the miss-match between the increased demand and the supply of iodine with the advancement of the pregnancy [ 15 ].…”
Section: Discussionsupporting
confidence: 88%
“…Various studies have shown that low iodine intake during pregnancy may result in hypothyroidism and brain damage (1,2).…”
mentioning
confidence: 99%
“…6 Another study conducted in New Delhi 19 and Haryana 20 showed median urinary iodine 150µg/L indicating dietary sufficiency. The study in Dhaka 21 showed that maternal urinary iodine is negatively correlated with their serum TSH. Similarly other study in Thailand 22 showed there was no co-relation between maternal urinary iodine and TSH.…”
Section: Urinary Iodine In Second Trimester Of Pregnancy: a Cross Secmentioning
confidence: 99%